(untitled) (Journal of Applied Business and Economics, 2025)
The study sought to identify Nigeria’s macroeconomic FDI drivers. It employed least square methods with model diagnostic tests and Granger causality processes on 1986–2020 Nigerian yearly data. The results show that interest rate, currency rate, and level of economic activity (represented by growth in real GDP) influence FDI into Nigeria. FDI is neither driven by inflation nor by international openness. The policy implications are that when considering policies aimed at attracting foreign direct investors to Nigeria, government and monetary authorities should prioritize such factors as interest rates, exchange rates and growth rate of the economy. Reduced loan rates and slight Naira depreciation should be promoted. Honest and concerted efforts are needed to keep the economy and aggregate output growing.